EXPERT EVALUATION METHOD OF RISKS OF SCIENTIFIC PROJECTS - Бедрій, Дмитро Іванович (Eastern-European Journal of Enterprise Technologies, 2013)
The article concerns the application of expert methods of evaluation of risks in the activity of scientific institutions of the public sector of economy. The main purpose of the study is the development of the methods to prevent and reduce the possibility of risks and negative events, and their impact on planning and implementation of research projects. The usage of the expert method for evaluation of risks of scientific projects allows project managers to collect and analyze information from experts in this area for timely decision-making. In this article, we discuss the results of the analysis of risks, affecting the planning and implementation of scientific projects, in order to use them further for quantitative risks analysis by means of the expert method. The method provides important information using conventional mathematical and statistical tools for analysis of risks of scientific projects. This method is suggested to provide timely and quality decision-making of a manager of a research project. We propose to use the expert method of evaluation of risks of scientific projects to find a consensus on the basis of different opinions of scientists, workers and managers of scientific projects. The research results can be used by expert scientists, planning and implementing scientific projects.